2021
DOI: 10.22376/ijpbs/lpr.2021.11.2.p146-152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wound Healing Activity of Catharanthus Roseus Aqueous Extract in Adult Albino Rats

Abstract: Use of plant extracts in the treatment of several ailments is a science known to the mankind since time immemorial. Yet, its popularity is limited owing to the lack of recorded experimental evidence to determine their potential health benefits. C. roseus is a traditional medicinal plant with over 100 identified alkaloids and several other phytochemicals known for various health promoting activities. The aim of the present study was to evaluate C. roseus aqueous extracts' wound healing potential using incision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, healing in the excisional wound group was delayed until the 14th day. The relevant studies (23)(24)(25)(26)(27) revealed that healing in the wound areas started from day three, and the healing rates were very high on day 7. The findings of the current study were consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, healing in the excisional wound group was delayed until the 14th day. The relevant studies (23)(24)(25)(26)(27) revealed that healing in the wound areas started from day three, and the healing rates were very high on day 7. The findings of the current study were consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were observed for half an hour after the administration of the drug. Prolongation of duration of seizure latency was taken as an index of protection & anticonvulsant activity of the test compound 17,18.…”
mentioning
confidence: 99%